Mucopolysaccharidoses: early diagnostic signs in infants and children - Cinzia Galimberti; Annalisa Madeo; Maja Di Rocco; Agata Fiumara (BMC, 2018)
Abstract Mucopolysaccharidoses (MPS) comprise a group of lysosomal disorders that are characterized by progressive, systemic clinical manifestations and a coarse phenotype. The different types, having clinical, biochemical, and genetic heterogeneity, share key clinical features in varying combinations, including joint and skeletal dysplasia, coarse facial features, corneal clouding, inguinal or abdominal hernias, recurrent upper respiratory tract infections, heart valve disease, carpal tunnel syndrome, and variable neurological involvement. In the severe forms, these features usually appear in the first months of life, but a correct diagnosis is often reached later when suggestive signs are manifest. All MPS types may have severe or attenuated presentations depending on the residual enzymatic activity of the patient. Based on data from the literature and from personal experience, here we underline the very early signs of the severe forms which should alert the paediatrician on their first appearance. A few early signs are typical of MPS (i.e. gibbus) while many are unspecific (hernias, upper airway infections, organomegaly, etc.), and finding the association of many unspecific signs might prompt the paediatrician to search for a common cause and to carefully look for other more specific signs (gibbus and other skeletal deformities, heart murmur). We stress the need to increase awareness of MPS among paediatricians and other specialists to shorten the still existing diagnostic delay. A timely diagnosis is mandatory for the commencement of treatment as soon as possible, when available, to possibly obtain better results.